Evaluation of outdoor environment of DSWD-accredited day care centers - Vergara, Eula S.; Quijano, Ma. Lourdes M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016.)
This descriptive-evaluative study examined and evaluated the physical outdoor environment of selected DSWD-accredited day care centers in Quezon City. The study (a) identified the man-made and natural components of the outdoor environment, (b) determined the characteristics of the components based on area, material, and physical safety, and (c) determined the changes to create an appropriate outdoor environment of day care centers. A qualitative approach was employed with on-site observation and interview as the data collection methods. Twenty-seven (27) day care centers were selected through purposive sampling. Eleven (11) child development workers were also interviewed for verification of observation. Results showed that eight (8) out of 27 DSWD-accredited day care centers have an existing outdoor environment. Findings identified four types of man-made components (cemented pavement, synthetic grass, seesaws, and swings) and three types of natural components (plants, trees, and a hanging garden). Evaluation based on area revealed that the existing space is inadequate for children's movements and exploration. Evaluation results based on material indicated the presence of man-made components that are made of metal, cement, and plastic while natural components are made of organic elements. Evaluation based on physical safety showed compliance on area's supervision and cleanliness. However, the safety evaluative features of the physical structure of the available man-made components are not present. The views of child development workers regarding an appropriate outdoor environment generally described a traditional playground that has adequate space for movement and sufficient number of age-appropriate playground equipment.
Thesis (Master of Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Day care centers -- Philippines